On the Welfare Analysis of Rational Expectations Equilibria with Asymmetric Information - Laffont, Jean-Jacques (Econometrica, 1985)
[Rational expectations equilibria are analyzed as incentive compatible mechanisms. The sense in which they can be implemented is made precise. Then, a welfare analysis of these equilibria is carried out within the class of mechanisms having the same incentive compatibility properties and the same communication constraints.]